1989
DOI: 10.1128/jvi.63.1.311-318.1989
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between organization of the actin cytoskeleton and the cell cycle in normal and adenovirus-infected rat cells

Abstract: Flow cytometry and staining with 7-nitrobenz-2-oxa-1,3-diazole-phallacidin were used to investigate organization of the actin cytoskeleton in rat embryo cells at different stages of normal and adenovirus ElA-induced cell cycles. In uninfected cells in GO-GI and S phases, actin was predominantly in the form of stress fibers. In G2, this organization changed to peripheral rings of thin filaments, while during mitosis, actin had a diffuse distribution. Infection of quiescent rat cells by adenovirus caused them to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Such varied activities as genome replication, protein synthesis and transport, and assembly, transport, and release of virions have been associated with these structures. Actin microfilaments in particular have been associated with the rounding and loss of adhesion that frequently occur with viral infection or transformation (6,16,19,24,29,43,47,59), with the intracellular transport of viral structural proteins and viral particles (1,21,49), with the budding process of many enveloped viruses (14,33,34,60), and with the assembly of virions in the cytoplasm (17,44) and in the nucleus (55).…”
mentioning
confidence: 99%
“…Such varied activities as genome replication, protein synthesis and transport, and assembly, transport, and release of virions have been associated with these structures. Actin microfilaments in particular have been associated with the rounding and loss of adhesion that frequently occur with viral infection or transformation (6,16,19,24,29,43,47,59), with the intracellular transport of viral structural proteins and viral particles (1,21,49), with the budding process of many enveloped viruses (14,33,34,60), and with the assembly of virions in the cytoplasm (17,44) and in the nucleus (55).…”
mentioning
confidence: 99%
“…In the present study, disruptions in S. littoralis gut morphology and disappearance of microfilament structures in actin ( Figure 6 ) could be a consequence of the phytoecdysteroid titers in the A. iva crude leaf extract. Actin microfilaments in particular have been associated with the rounding and loss of adhesion that frequently occur with viral infection or transformation in response to secondary metabolites [ 51 , 52 ], with the intracellular transport of viral structural proteins and viral particles [ 53 ], with the budding process of many enveloped viruses [ 54 ], and with the assembly of virions in the cytoplasm [ 55 ] and in the nucleus [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histological observations of the gut showed that S. littoralis is Figure 6) could be a consequence of the phytoecdysteroid titers in the A. iva crude leaf extract. Actin microfilaments in particular have been associated with the rounding and loss of adhesion that frequently occur with viral infection or transformation in response to secondary metabolites [56,57], with the intracellular transport of viral structural proteins and viral particles [58], with the budding process of many enveloped viruses [59], and with the assembly of virions in the cytoplasm [60] and in the nucleus [61].…”
Section: Discussionmentioning
confidence: 99%